Effect of angle of incidence on stability derivatives of a wing - Crasta, Asha; Khan, Sher Afghan (http://www.ijraset.com/fileserve.php?FID=491, 2014)
In the Present paper effect of angle of incidence on pitching derivatives of a delta wing with curved leading edges of a attached shock case is been studied. A Strip theory is used in which strips at different span wise location are independent. This combines with similitude to give a piston theory. From the results it is found that stiffness and damping derivatives in pitch increasing linearly up to angle of attack 250 and then non-linearity creeps in. The Present theory is valid only for attached shock case. Effects of wave reflection and viscosity have not been taken into account. Results have been obtained for hypersonic flow of perfect gases over a wide range of angle of attack and Mach number.